The Influence of Islamic Attributes on Consumer Satisfaction and Loyalty Through Religiosity as a Mediating Variable in Sharia Hotels in Kendari City - Waode Maratun Shaleha (Jurnal Ilmiah Ekonomi Islam, 2023)
In Kendari city, there are five Shariah hotels, namely Hotel Zahra Syariah, Hotel Azizah Syariah, Hotel Kubah 9, Hotel Liras Syariah, and Tropical Point Hotel Syariah. The purpose of this research is to examine the influence of religiosity variables on consumer loyalty with Islamic attributes and customer satisfaction as mediating variables. The sampling technique used in this research is accidental sampling. The sample size in this study is 215 respondents, obtained using the Slovin formula. The results of this research indicate that Islamic physical attributes have a significant positive effect on customer satisfaction, while Islamic non-physical attributes have a non-significant negative effect on customer satisfaction. Islamic religiosity mediates the influence of Islamic physical attributes on customer satisfaction with a non-significant negative effect. Religiosity mediates the influence of Islamic non-physical attributes on customer satisfaction, which has a significant positive effect. Religiosity mediates the influence of customer satisfaction on behavioral loyalty with a non-significant positive effect. Islamic religiosity mediates the influence of customer satisfaction on attitudinal loyalty with a significant positive effect. Customer satisfaction has a significant positive effect on behavioral loyalty, and customer satisfaction also has a significant positive effect on attitudinal loyalty.